The Influence of Organizational Communication and Work Motivation on Employee Performance - Namaradzani, Fiqri Ikbal; Jamaludin, Asep; Nandang, Nandang (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
The purpose of this study was to determine and analyze 1) The effect of Organizational Communication on Employee Performance in the finished goods section of PT Pindo Deli Pulp And Paper Mills Karawang, 2) The influence of Work Motivation on Employee Performance of the finished goods section of PT Pindo Deli Pulp And Paper Mills Karawang, 3) The Effect of Organizational Communication and Work Motivation on Employee Performance of the finished goods section of PT Pindo Deli Pulp And Paper Mills Karawang. The method used in this research is an explanatory survey method with a population of 134 employees and a sample size of 90 respondents, while the analytical tools used are multiple regression analysis, coefficient of determination, hypothesis testing and significance testing. The results of this study found that organizational communication has a significant positive effect on the performance of employees of the finished goods section of PT Pindo Deli Pulp And Paper Mills Karawang. Work motivation has a significant positive effect on the performance of employees of the finished goods section of PT Pindo Deli Pulp And Paper Mills Karawang. Organizational communication and work motivation together have a significant positive effect on the performance of employees of the finished goods section of PT Pindo Deli Pulp And Paper Mills Karawang. Further research is recommended to consider other variables that can affect employee performance besides organizational communication and work motivation. In the future, it can add independent variables such as leadership style, work environment. In addition, it can increase the research subject to all employees at PT Pindo Deli Pulp And Paper Mills Karawang, not only the finished goods section.  Because organizational communication affects employee performance at PT Pindo Deli Pulp And Paper Mills Karawang with a positive relationship direction, the company must ensure that information about the vision, mission and goals of the organization is clear and accessible to all employees. Provide a transparent forum or communication channel to convey organizational information to all members. Work motivation has a significant positive effect on the performance of employees in the finished goods section of PT Pindo Deli Pulp And Paper Mills Karawang, so companies must adopt a holistic approach that involves various aspects of employee work life. Recognize individual needs and desires while maintaining fairness and transparency.